The Influence Of Organizational Fairness, Organizational Culture and Job Satisfaction On Organizational Commitment - Tegar Hidayat, Tegar Hidayat; Subiyanto, Didik; Septyarini, Epsilandri (Profesional Muda Cendekia Publishing, 2024)
Research Aims: This study aims to analyze the effect of organizational justice, organizational culture, and job satisfaction on organizational commitment among community members of Kampung Batik Giriloyo, Wukirsari, Bantul, DIY. Design/methodology/approach: This study is a quantitative research, by examining the cause-and-effect relationship of the variables Organizational Justice, Organizational Culture, Job Satisfaction, and Organizational Commitment, with 42 respondents. Data was collected using a questionnaire using a Likert scale of 1 to 5, where 1 indicated